Improving HIV test uptake and case finding with assisted partner notification services - Dalal, Shona; Johnson, Cheryl; Fonner, Virginia; Kennedy, Caitlin E; Siegfried, Nandi; Figueroa, Carmen; Baggaley, Rachel (AIDS (London), 2017)
Despite the enormous expansion of HIV testing services (HTS), an estimated 40% of people with HIV infection remain undiagnosed. To enhance the efficiency of HTS, new approaches are needed. The WHO conducted a systematic review on the effectiveness of assisted partner notification in improving HIV test uptake and diagnosis, and the occurrence of adverse events, to inform the development of normative guidelines. We systematically searched five electronic databases through June 2016. We also contacted experts in the field and study authors for additional information where needed. Eligible studies compared assisted HIV partner notification services to passive or no notification. Where multiple studies reported comparable outcomes, meta-analysis was conducted using a random-effects model to produce relative risks (RRs) or risk ratios and 95% confidence intervals (CIs). Of 1742 citations identified, four randomized controlled trials and six observational studies totalling 5150 index patients from eight countries were included. Meta-analysis of three individually randomized trials showed that assisted partner notification services resulted in a 1.5-fold increase in HTS uptake among partners compared with passive referral (RR = 1.46; 95% CI: 1.22-1.75; I = 0%). The proportion of HIV-positive partners was 1.5 times higher with assisted partner notification than with passive referral (RR = 1.47; 95% CI: 1.12-1.92; I = 0%). Few instances of violence or harm occurred. Assisted partner notification improved partner testing and diagnosis of HIV-positive partners, with few reports of harm. WHO strongly recommends voluntary assisted HIV partner notification services to be offered as part of a comprehensive package of testing and care.